(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This report presents a mentoring experience for the elaboration of extensionist workshops held in Module 4 of the University Extension, Curriculum and Society course, promoted by the Extensionist Rondon Nucleus of the State University of Santa Catarina (NER / UDESC) during the year 2020. Furthermore, the intention is to maintain the memory of the works carried out in the face of the challenge of virtual production of workshops in the Environment and Work Area. The writing methodology used was the logic of qualitative research, non-systematic bibliography and observation carried out concurrently with the development of the project, in addition to the collection of testimonials from course participants through an electronic form. As a result, it is highlighted that there were several contributions to course participants, above all, the opportunity for training and experience. Finally, there is also the record of a historic moment of effort by University Extension and the experience of mentoring mediated through cyberspace, which proved to be very promising for future mediations.